2008
DOI: 10.1063/1.2834275
|View full text |Cite
|
Sign up to set email alerts
|

Thermal effects on Farley–Buneman waves at nonzero aspect and flow angles. I. Dispersion relation

Abstract: With the increasingly accepted notion that E-region electrostatic plasma waves move at their instability threshold speed when they attain their maximum amplitude, it has become more important to determine just what that threshold speed is supposed to be. An accurate determination requires a calculation of the electron temperature fluctuation level, which can sometimes dramatically influence the results. In this paper, the Grad 8-moment transport equations have been employed with the addition of a generalized e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 26 publications
1
26
0
Order By: Relevance
“…We have analyzed the results of experimental studies of Farley‐Buneman waves over Jicamarca by probing the equatorial electrojet at Bragg's scales 3 and 0.35 m. We have shown that the advanced linear theory [ Kagan and St.‐Maurice , 2004; Kissack et al , 2008a, 2008b] explains well the altitude dependence of V ph for JULIA vertical, 23‐ and 51‐degree west transmissions, and observations of AMISR‐P at 0 and 20 degrees west. The remarkable match of the linear theory predictions to observations seems to further confirm the long suspected fact that whatever the nonlinear process generating FB waves is, it produces waves moving at their linear threshold speed.…”
Section: Discussionmentioning
confidence: 99%
“…We have analyzed the results of experimental studies of Farley‐Buneman waves over Jicamarca by probing the equatorial electrojet at Bragg's scales 3 and 0.35 m. We have shown that the advanced linear theory [ Kagan and St.‐Maurice , 2004; Kissack et al , 2008a, 2008b] explains well the altitude dependence of V ph for JULIA vertical, 23‐ and 51‐degree west transmissions, and observations of AMISR‐P at 0 and 20 degrees west. The remarkable match of the linear theory predictions to observations seems to further confirm the long suspected fact that whatever the nonlinear process generating FB waves is, it produces waves moving at their linear threshold speed.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of aspect sensitivity of Farley‐Buneman waves by Jackel et al [1997, 2002] with a coherent scatter radar showed that the FB aspect angle observed in the equatorial electrojet (as opposed to auroral region) was confined within less than ∼3° off the boldB0 ‐perpendicular direction. The FB theory that included electron thermal corrections by Kagan and St. ‐ Maurice [2004] and Kissack et al [2008a, 2008b] predicted the Farley‐Buneman aspect sensitivity to be within ∼2.5°. Using the large Jicamarca radar and advanced analysis techniques, Kudeki and Farley [1989] demonstrated that the aspect angle of the FB waves deviated by angles between 0.1° and 0.4°.…”
Section: Ionospheric Plasma Instabilitymentioning
confidence: 99%
“…More recently Kissack et al (2008a) and Kissack et al (2008b) have written papers discussing in great detail thermal effects and their relation to aspect angles and flow angles. The problem with this is that it is dangerous to assume large flow angles, in particular, since, as we have seen, large scale velocities and electric fields are likely to be quite turbulent, at least at the equator, and radars will always respond most strongly to the regions where the flow angle is small.…”
Section: Kinetic Theory Calculationsmentioning
confidence: 99%